2002
DOI: 10.2460/javma.2002.221.651
|View full text |Cite
|
Sign up to set email alerts
|

Use of carbon dioxide laser for onychectomy in cats

Abstract: The CO2 laser can be an excellent tool for onychectomy in cats, with excellent hemostasis and minimal postoperative discomfort and complications. Differences in discomfort and complications between groups treated via scalpel versus CO2 laser were not clinically relevant and were only observed 1 day after surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 6 publications
2
24
0
Order By: Relevance
“…The most frequently reported AEs included surgical site bleeding, infected surgery sites, inappetance, and lethargy, complications typically associated with surgery. Reported incision site bleeding was restricted to the onychectomy site and is consistent with the report that 50% of onychectomy surgeries have complications including pain, bleeding, and lameness, regardless of onychectomy technique [19, 20]. At supratherapeutic (5 or 10 mg/kg) dosages daily for 28 days, robenacoxib was well tolerated and had no detectable effect on the partial activated prothromboplastin time or hematology variables in healthy young cats [7].…”
Section: Discussionsupporting
confidence: 70%
“…The most frequently reported AEs included surgical site bleeding, infected surgery sites, inappetance, and lethargy, complications typically associated with surgery. Reported incision site bleeding was restricted to the onychectomy site and is consistent with the report that 50% of onychectomy surgeries have complications including pain, bleeding, and lameness, regardless of onychectomy technique [19, 20]. At supratherapeutic (5 or 10 mg/kg) dosages daily for 28 days, robenacoxib was well tolerated and had no detectable effect on the partial activated prothromboplastin time or hematology variables in healthy young cats [7].…”
Section: Discussionsupporting
confidence: 70%
“…) and pain scores were significantly lower (Mison et al. ) following onychectomy performed with a laser rather than a scalpel. Cats were also more lame when the surgeon had used a scalpel (Holmberg & Brisson ).…”
Section: Resultsmentioning
confidence: 99%
“…In two of these studies, lameness was scored as part of a composite pain score and was not reported separately (Mison et al. ; Curcio et al. ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations